2015
DOI: 10.1002/2014wr015840
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of multiple local peaks in breakthrough curves

Abstract: The analysis of breakthrough curves (BTCs) is of interest in hydrogeology as a way to parameterize and explain processes related to anomalous transport. Classical BTCs assume the presence of a single peak in the curve, where the location and size of the peak and the slope of the receding limb has been of particular interest. As more information is incorporated into BTCs (for example, with high-frequency data collection, supercomputing efforts), it is likely that classical definitions of BTC shapes will no long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…We note also that Siirila‐Woodburn et al . [] presented 3‐D high‐resolution simulations of tracer migration in synthetic domains with geostatistically based, heterogeneous hydraulic conductivities. Particle tracking simulations were used to generate BTCs; they demonstrated the appearance of multiple (local) peaks in single realizations, and showed that the number and slopes of local peaks depend on statistical anisotropy and travel distance.…”
Section: Resultsmentioning
confidence: 99%
“…We note also that Siirila‐Woodburn et al . [] presented 3‐D high‐resolution simulations of tracer migration in synthetic domains with geostatistically based, heterogeneous hydraulic conductivities. Particle tracking simulations were used to generate BTCs; they demonstrated the appearance of multiple (local) peaks in single realizations, and showed that the number and slopes of local peaks depend on statistical anisotropy and travel distance.…”
Section: Resultsmentioning
confidence: 99%
“…The PT 100M BTC is considered the ''true'' transport solution, or as closely to the true solution which is numerically feasible at this time, although we acknowledge the true solution will only be achieved with an infinite number of particles. Following the approach described in Siirila-Woodburn et al [2015], the estimated 95% confidence interval of the PT 100M BTC was found to be smaller than about 10 28 for all times. To quantify how much the PT and KDE BTCs differ from the high resolution result, an integrated root-meansquare error (IRMSE) metric is calculated given the solute concentration measures {C(t 1 ),.…”
Section: Reconstruction Of Unaveraged Btcs C Versus T and Associatementioning
confidence: 93%
“…Representative BTC I (Figure 2a) is nearly Gaussian, showing somewhat ideal Fickian conditions. Representative BTCs II-IV (Figures 2d, 2g, and 2j) show some degree of anomalous behavior, displaying a number of local peaks of different duration in time [Siirila-Woodburn et al, 2015]. BTC IV (Figure 2j) resembles a power-law like curve.…”
Section: Representative Btcsmentioning
confidence: 99%
See 1 more Smart Citation
“…and Tsang (1991), Siirila-Woodburn et al (2015), and Boon et al (2017). More precisely, assuming a single-pulse tracer injection signal, multimodal BTCs reflect a three-step process: 1) tracer spreading into different flowing or nonflowing aquifer subdomains characterized by different transit/residence times, 2) tracer motion within each subdomain with little or no exchange between the different subdomains, and 3) convergence (mixing) of the subtracer fluxes somewhere upstream from, 65 or at, the monitoring point.…”
mentioning
confidence: 95%